2017
DOI: 10.1016/j.oregeorev.2016.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur and strontium isotopic study of epithermal mineralization: A case study from the SE Afar Rift, Djibouti

Abstract: Epithermal mineralization was recently described in synrift volcanic rocks from the SE Afar Rift in Djibouti. To infer fluid sources in this system, coupled sulfur and strontium isotopic analyses were performed on mineralized samples from hydrothermal veins and stockwork zones. Mineralization includes gypsum and chalcedony, and/or quartz ± carbonate containing gold and sulfides. Sulfur isotopic compositions of sulfides and sulfates were determined using Multicollector-Inductively Coupled Plasma Mass Spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…In our hydrothermal sites, pyrite and chlorite have been described at Ali Addé and Hes Daba sites. Therefore, it is here suggested that gold could have been transported as bisulfide complexes in Hes Daba and Ali Addé areas although multiple sources of fluids are documented in these sites (Moussa et al, 2017). Furthermore; Moussa et al, 2012 reported two different stages of hydrothermal ore deposits: i) the first stage corresponds to massive quartz -containing sulfide minerals; ii) the second stage is characterized by the formation of chalcedony gangue containing gold and sulfide minerals.…”
Section: Fluid Inclusionsmentioning
confidence: 83%
See 2 more Smart Citations
“…In our hydrothermal sites, pyrite and chlorite have been described at Ali Addé and Hes Daba sites. Therefore, it is here suggested that gold could have been transported as bisulfide complexes in Hes Daba and Ali Addé areas although multiple sources of fluids are documented in these sites (Moussa et al, 2017). Furthermore; Moussa et al, 2012 reported two different stages of hydrothermal ore deposits: i) the first stage corresponds to massive quartz -containing sulfide minerals; ii) the second stage is characterized by the formation of chalcedony gangue containing gold and sulfide minerals.…”
Section: Fluid Inclusionsmentioning
confidence: 83%
“…As such, it has been the focus of intense geological and geophysical investigations that resulted in a number of propagation rift models principally devoted to the last myrs rift history in SE Afar (Manighetti et al, 1997;Audin et al, 2001;Daoud et al, 2011). These tectono-magmatic models have been recently completed by integrating hydrothermal aspects that emphasized the role of dominantly magma-related fluids in the occurrence of epithermal ore deposits (Moussa et al 2012;2017). These occurrences are mainly represented by base metal and precious metals-bearing quartz/carbonate ±adularia veins (Moussa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measured 87 Sr/ 86 Sr ratios of Sakallol-Harallol chimneys are consistent with Sr isotope compositions of hot spring waters in this area (0.70365 -0.70626; Awaleh et al, 2017) and Djibouti basalts (0.70309 -0.70664; Vidal et al, 1991;Barrat et al, 1993;Deniel et al, 1994;Faure, 2001). More recently, Moussa et al (2017) investigated Sr isotopes of chalcedony-quartz veins (0.7032 and 0.7072), suggesting that Sr was derived from different sources of fluids, such as magmatic, hydrothermal and seawater.…”
Section: J O U R N a L P R E -P R O O F 15mentioning
confidence: 99%
“…1A) (Stieljes, 1973;De Chabalier and Avouac, 1994;Deniel et al, 1994;Pinzutti et al, 2013). Over the last decades, the discovery of many hot springs and fumaroles in this region has fostered major interest in geothermal exploration (Fontes et al, 1989;San Juan et al, 1990;D'Amore et al, 1998;Awaleh et al, 2015a, b;2017). Since the 1970s, many hydrothermal structures have also been identified in the lakes that are aligned along the rift system (e.g.…”
Section: Introductionmentioning
confidence: 99%